Grupo de pais no psicodiagnóstico colaborativo : uma compreensão fenomenológica existencial - Biselli, Andréa Cristina Tavelin (2013)
This study arises from the author s concerns lived within the experience of psychological practice with groups of parents and children in collaborative psychodiagnostic, in a phenomenological existential perspective. It aims to understand the experience of parents in a group with that modality of psychological practice. It s phenomenal basis is grounded in four reports of parents who have experienced group care in the process of Collaborative Psychodiagnostic carried out in Pernambuco s Catholic University clinic-school between 2010 and 2012. To access such experience, subjects-collaborators were submitted to a narrative interview. As an instrument, the narrative interview is based on the narrator idea by Walter Benjamim (1994) which, articulating narrative and experience, allows the narrator (participant) to elaborate and pass on experiences regarding the investigated theme. Another instrument was a logbook (a field journal), which is constituted by written narratives of feeling and impressions lived by the researcher in listening to its clients. Analysis was centered in Gadamer s hermeneutic philosophy, considered to be one the privileged epistemologies in qualitative research. The dialog, the conversations among psychologist and clients and also among clients, who were open to put themselves in such a comprehensive dynamic, allowed the complaint to be broaden, which led to the demands elicitation and appropriation by merging collaborators horizons. At first, the parents group situation in collaborative psychodiagnostic enabled the appropriation and expression of affective dispositions of fear and resistance face to an unknown condition. Living a group experience has affected each participant leading them to another way of being in and feeling the group situation, which was then perceived as welcoming and facilitator for the expression of sufferings and feelings. Such motion provided participants to understand manifested complaint, enabling their feelings to be appropriated with the thematization of other comprehensive possibilities, allied to the movement of openness towards the other, at the same time that allowed the decentralization in each one s problems, previously considered as unique. At last, the narrative of experiences is highlighted as a facilitator for the appropriation of the way in which participants took care of themselves and of others in this case, their families. It was noticed that the appropriation of an affective and singular experience could put in motion other ways of being and relating with the world and with others, ways of their own, less orientated by the public.